Mineral, Rumensin®, and chlortetracycline supplementation for steers on native bluestem pasture - E.F. Smith; Jack G. Riley; R.R. Schalles; Ronald W. Graber; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1985)
Eighty steers, primarily of British breeding, were allotted to one of four treatments and maintained on native bluestem pastures from January 11, 1984 to October 2, 1984. Steers received either chlortetracycline or Rumensin®, with and without mineral supplementation.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Mineral; Rumensin®; Chlortetracycline; Bluestem